2020
DOI: 10.1111/mec.15439
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ion transport and energy metabolism enables certain coral genotypes to maintain calcification under experimental ocean acidification

Abstract: The ocean absorbs about one-third of anthropogenic carbon dioxide (Sabine et al., 2004), resulting in a decrease in oceanic pH. As pH drops, the concentration of carbonate ions decreases. Together, carbonate ion availability and pH exert a strong influence over the rates of calcification in organisms that use calcite or aragonite for skeletal, test, and shell formation (Georgian, DeLeo, et al., 2016;Melatunan, Calosi, Rundle, Widdicombe, & Moody, 2013;Waldbusser et al., 2015). The aragonite saturation horizon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 94 publications
1
11
0
Order By: Relevance
“…Although calcifiers can exhibit compensatory responses (e.g., phenotypic plasticity) to counter the impacts of climate change (Leung et al, 2017;Peck et al, 2018;Glazier et al, 2020;Wang et al, 2020), trade-offs against other biological processes are often incurred. For instance, the coral Galaxea fascicularis can accommodate OA by sustaining photosynthetic performance, but the nitrogen fixation machinery is compromised as a trade-off, possibly affecting coral resilience to OA (Zheng et al).…”
Section: Summary Of the Studies In This Special Issuementioning
confidence: 99%
“…Although calcifiers can exhibit compensatory responses (e.g., phenotypic plasticity) to counter the impacts of climate change (Leung et al, 2017;Peck et al, 2018;Glazier et al, 2020;Wang et al, 2020), trade-offs against other biological processes are often incurred. For instance, the coral Galaxea fascicularis can accommodate OA by sustaining photosynthetic performance, but the nitrogen fixation machinery is compromised as a trade-off, possibly affecting coral resilience to OA (Zheng et al).…”
Section: Summary Of the Studies In This Special Issuementioning
confidence: 99%
“…Here, the notable decreases in shell length and width under the elevated temperature and pCO 2 (20 • C × 1000 ppm) scenario support these previous findings, suggesting depression of some energetically expensive processes (i.e., soft tissue maintenance) and up-regulation of other physiological and biochemical functions. The observed increases in shell length and width under elevated pCO 2 and ambient temperature conditions (17 • C × 1000 ppm) also suggests that mussels may have some capacity to up-regulate biomineralization to maintain or grow shell material under OA (Bibby et al, 2007;Melatunan et al, 2013;Coleman et al, 2014, but see Leung et al, 2020; a process that may be driven by an up-regulation of ion and proton transport genes associated with organic matrix formation (Glazier et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A link between ultrastructure disruption and reduced expression of calcification proteins under elevated pCO 2 has been proposed (e.g., Huning et al, 2013;Fitzer et al, 2014b), although shell matrix protein candidate genes and the expression of carbonic anhydrase -the latter of which catalyzes the interconversion of bicarbonate and CO 2 -appear less affected by elevated CO 2 (Huning et al, 2013). Furthermore, our understanding of the interaction between protein expression, functioning, and CaCO 3 formation remains limited (see Glazier et al, 2020 for a recent study in corals). A number of models have been proposed including: changes in epitaxial growth, the formation of "mineral bridges" between crystals, or alteration of the c-axis (0001 plane) orientation during the earlier stages of crystal formation (Choi and Kim, 2000;Checa et al, 2006;Fryda et al, 2010;Olson et al, 2013;Maier et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variation that influences gene expression during development could, in principle, provide genotypes that facilitate adaptation to OA in natural populations (Glazier et al., 2020; Goncalves et al., 2016; Pespeni et al., 2013; Runcie et al., 2016). A previous study found that development and settlement success of H. erythrogramma under OA conditions were both strongly influenced by male parent (Foo et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variation that influences gene expression during development could, in principle, provide genotypes that facilitate adaptation to OA in natural populations (Glazier et al, 2020;Goncalves et al, 2016;Pespeni et al, 2013;Runcie et al, 2016).…”
Section: Molecular Responses To Oa Are Eclipsed By the Impact Of Namentioning
confidence: 99%